PERSEPSI PELAKU EKONOMI KULINER TENTANG SURAT REKOMENDASI MAJELIS ULAMA INDONESIA (MUI) SUMATERA BARAT PERIHAL PENGGUNAAN NAMA USAHA KULINER - Yogi Harian Nanda; Elsy Renie (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This study examines the perception of culinary economists on letters of recommendation from the Indonesian Ulema Council (MUI) West Sumatra regarding the prohibition of culinary names that are not in accordance with Islamic law. The type of research used is field research, with exploratory qualitative methods. Sources of data in this study consisted of primary data and secondary data. The findings from this study are that the majority of producers and consumers of culinary businesses do not agree with the recommendation letter from the Indonesian Ulema Council (MUI) West Sumatra regarding the use of culinary business names and do not even care about the letter, because they consider the recommendation letter from the Indonesian Ulema Council (MUI) at the West Sumatra level. This is not a type of statutory regulation that has binding law.